Medical biotechnology - Glick, Bernard R.; Delovitch, T. L.; Patten, Cheryl L. (ASM Press, 2014)
The future is now-this groundbreaking textbook illustrates how biotechnology has radically changed the way we think about health care.
Keywords: Biotechnology.; Medical technology.; Biomedical engineering.; elektronické knihy; electronic books